Optimization of Deodorization Process and Analysis of Fishy Aftertaste Substances in Pangasius bocourti Fillets - Jiali BAO; Xubo FANG; Xiaoe CHEN; Suting LIU; Fang ZHANG; Junying SHEN (Shipin gongye ke-ji, 2022)
In order to ameliorate the fishy aftertaste and value addition of Pangasius bocourti fillets, this article used Perilla frutescens water extract for deodorization. The fishy aftertaste and color difference were used as indicators, combined with electronic nose auxiliary analysis to conduct single-factor experiments. Afterwards, the deodorization process parameters were optimized by orthogonal experiments. GC-MS was used to distinguish the differences in volatile compounds before and after deodorization of Pangasius bocourti fillets. After analyzing the experimental results, it was found that with the help of the electronic nose, the best process conditions for deodorization of Pangasius bocourti fillets were: The concentration of Perilla frutescens aqueous extract was 3%, the deodorization time was 60 min, and the deodorization temperature was 20 ℃. Under this condition, the fish fillets had no obvious fishy aftertaste, and the flesh was white and had a light Perilla frutescens fragrance. After soaking in Per